Analisis Perencanaan Kebutuhan Bahan Baku untuk Meminimakan Kekurangan Persediaan dan Memenuhi Kebutuhan Konsumen - Alvian Nikoverdiansah; Siti Mundari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
UD. Raga Jati is a business engaged in handicraft production using teak wood as the main raw material. The company produces various types of handicrafts such as tissue boxes, mini mineral water racks, trays, wooden cups, and other products. The problem faced by the company is the frequent shortage of raw materials, which causes financial losses and has the potential to result in customer loss. Based on the results of the Silver-Meal method, the company can place raw material orders twice a year. The first order is made in July to cover the January–June period with an order quantity of 5,211 pcs and an ordering cost of Rp.1,675,859. The second order is placed in December to cover the August–November period with an order quantity of 5,307 pcs and an ordering cost of Rp.1,292,607. The safety stock calculation results indicate that the company should maintain a safety stock of 58 pcs. Based on the reorder point calculation, the company should reorder raw materials when the inventory remaining in the warehouse reaches 664 pcs. Furthermore, the company experienced total losses amounting to Rp.95,494,000 during 7 periods within one year.